STUDI EKSPERIMENTAL PENGARUH PENAMBAHAN RESIN PADA AGREGAT KASAR TERHADAP KEKUATAN BETON - Bunga Sri Puspitasari; Muh. Alwi Umar; Sri Tudjono; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
It is well known that compressive strength of concrete is affected by the strength of the constituent materials and the strength of interfacial transition zone (ITZ). This research aimed at investigating the influence of the addition of resin on coarse aggregates on the strength of concrete. The resin investigated in this research was unsaturated polyester resin. The resin was combined with methanol with different composition of 1:0; 1:0.25; 1:0.5; and 1:1. The tests conducted in this investigation were pull off test, shear test and compression test. Test results show that all specimens with resin exhibit lower strength values compared to specimens with no resin. The compressive strength of concrete silinders with resin coated aggregates were obtained to be 16.26 MPa and 3.14 MPa, while the compressive strength of normal concrete ( with no resin) was 29.99 MPa.